MANAJEMEN PEMBIAYAAN PENDIDIKAN MENUJU PENDIDIKAN YANG BERMUTU - Dewi Lyien Ien; Ahmad Faqih Badrul M (ICO EDUSHA, 2023)
This research aims to determine the implications of financing management for improving the quality of education. This research uses a type of library research or what is usually called library research, where the data in this research comes from various literature, both physical data (books, magazines, newspapers, etc.) and online media. The research data obtained in this study was then studied using a theoretical and philosophical approach. The results of this research are the classification of activities, determining standardization, and determining unit costs in education budgeting. Education financing management has three important stages, namely planning, implementation stage and assessment (evaluation) stage. When applied to financial management, these three stages are the financial planning (budgeting) stage, the implementation (accounting) stage, and the assessment or auditing stage. With the education financing management system, it is hoped that it will be able to support and guarantee the development of the quality of education and the process of organizing teaching and learning activities. Keywords: Education Financing Management, Education Quality References Adlini, Miza Nina, Anisya Hanifa Dinda, Sarah Yulinda, Octavia Chotimah, and Sauda Julia Merliyana. “Metode Penelitian Kualitatif Studi Pustaka.” Edumaspul: Jurnal Pendidikan 6, no. 1 (2022): 974–980. Asrita, Riswel. “Manajemen Mutu Pendidikan Islam.” Hijri 11, no. 2 (2022): 159. Fadli, Muhammad Rijal. “Memahami Desain Metode Penelitian Kualitatif.” Humanika 21, no. 1 (2021): 33–54. Mesiono, Mesiono, Suswanto Suswanto, Rahmat Rifai Lubis, and Haidir Haidir. “Manajemen Pembiayaan Pendidikan Dalam Meningkatkan Mutu Pendidikan Di Madrasah Aliyah Imam Muslim Serdang Bedagai.” Intiqad: Jurnal Agama dan Pendidikan Islam 13, no. 1 (2021): 119–134. Nuriah, Fitri Syifa, and Deca Deca. “Pengelolaan Dan Pengalokasian Dana Di Lembaga Pendidikan.” Jurnal Global Futuristik 1, no. 2 (2023): 168–175. Rosdiana Kapu, Maya. “Manajemen Pembiayaan Dan Sarana Prasarana Laboratorium IPA Di SMP Negeri Satap Kangeli.” Prosiding Dewantara Seminar Nasional Pendidikan (2023): 01. Salsabila, Shinta. “Pengelolaan Manajemen Keuangan Guna Meningkatkan Sarana Dan Prasarana Yang Ada Di SDN Tembok Dukuh 3 Surabaya.” Dewantara: Jurnal Pendidikan Sosial … 2, no. 2 (2023): 261–268. Supriatna, Dasep, Nasrudin Harahap, and Nurul Hidayati Murtafiah. “Implikasi Manajemen Pembiayaan Terhadap Peningkatan Mutu Pendidikan.” Journal on Education 05, no. 04 (2023): 17296–17307.